Do Regulators Consider Welfare When Assigning Spectrum Via Comparative Selections? - Madden, Gary; Tran, Thien (Routledge, 2013)
This study asks whether regulators consider societal welfare in assigning radio spectrum via comparative selections and also whether assignment competitiveness matters to regulators. The short answers are that regulators do focus on welfare goals in short and medium terms and vehicles to achieve these goals are fees and deployment obligations, respectively. Attempts are also made to reduce entry barriers via financial obligations. Also evident is that competitive assignments are desired by regulators.